2005
DOI: 10.1038/sj.ijir.3901424
|View full text |Cite
|
Sign up to set email alerts
|

Linking erectile dysfunction and coronary artery disease

Abstract: Coronary artery disease (CAD) and erectile dysfunction (ED) are both highly prevalent conditions that frequently coexist. Additionally, they share mutual vascular risk factors, suggesting that they are both manifestations of systemic vascular disease. The role of endothelial dysfunction in CAD is well established. Normal erectile function is primarily a vascular event that relies heavily on endothelially derived, nitric oxide-induced vasodilation. Accordingly, endothelial dysfunction appears to be a common pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 79 publications
3
29
0
Order By: Relevance
“…Also, it is demonstrated that ED is an early symptom or harbinger of cardiovascular disease, owing to the Sexual dysfunction in women with coronary artery disease C Kaya et al common risk factors and pathophysiology mediated through endothelial dysfunction. 20 The present study revealed that two-thirds of women with proven CAD have FSD, which was considered comparable to the previous studies on SD and heart diseases.…”
Section: Discussionsupporting
confidence: 74%
“…Also, it is demonstrated that ED is an early symptom or harbinger of cardiovascular disease, owing to the Sexual dysfunction in women with coronary artery disease C Kaya et al common risk factors and pathophysiology mediated through endothelial dysfunction. 20 The present study revealed that two-thirds of women with proven CAD have FSD, which was considered comparable to the previous studies on SD and heart diseases.…”
Section: Discussionsupporting
confidence: 74%
“…At the subcellular level, the underlying mechanism is based on the impaired bioavailability of nitric oxide (NO) that compromises normal NO-mediated vasodilatation. This condition favors vasoconstriction, deregulates intima proliferation, and promotes a proinflammatory environment that cause plaque destabilization (Rodriguez et al 2005). Endothelial dysfunction is thus considered a basic initiator in the formation of atheroma plaque (Marx and Grant 2007), and therefore, it precedes the clinical manifestations of atherosclerosis (Boneti et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Erectile dysfunction is a commonly under-diagnosed disease entity that shares common risk factors and pathophysiologic mechanisms with cardiovascular disease, 9 affecting approximately 30 million men in the United States. 10,11 One of the early studies to assess the prevalence of sexual dysfunction was Figure 4 Responses from male and female heart failure patients whether they are interested in treatment to improve their current sexual dysfunction.…”
Section: Sexual Dysfunction In Generalmentioning
confidence: 99%